Welfare and physiological stress responses in cattle due to effects of sea and road transportation in tropical climate - Abubakar, Ahmed Abubakar (2018)
Currently, there is an increasing global demand for meat. However, animal welfare legislation in many developing countries is not fully implemented and therefore remains debatable on how animals should be handled, loaded, transported, unloaded, and time to spend in lairage and slaughter without causing unnecessary pain or distress. Therefore, stress induced by transport is very important in meat production; whose time and or mismanagement pose some risks to both animal welfare and meat quality. In fact, transportation does not only affect animal welfare, but it can also negatively influence meat quality or worse still, cause economic losses. The impact of stress on animal welfare is too important to ignore and this makes it necessary to control and minimise transport related stress-inducing factors for ethical, quality and economic reasons. There is dearth of scientific information on the effects of sea and road transport on welfare, physiological stress response and electroencephalogram. Therefore, the current study was aimed at evaluating the effects of sea and road transport on physiological stress responses, electroencephalogram in compliance with animal welfare ethics. The current study, describes the link between blood biochemistry, hematology, neuroendocrine, and acute phase proteins (APP), typical characteristics associated with possible stress with electroencephalogram (EEG) activities after subjecting animals to sea and road transport and effects on welfare. Sixty (60) heifers of Brahman crossbred were subjected to a 14 d transport by sea and 14 h of road transport.Blood analysis revealed that the intensity of response for most biochemical blood parameters - alanine transaminase, aspartate transaminase and creatinine kinase significantly increased (p<0.05) and were different from the baseline values taken while animals were in Darwin Port, Australia. Hematological results obtained also revealed that the (White blood cells, Red blood cells, neutrophils and lymphocytes) increased significantly (p<0.05) and were different from the baseline values taken while animals were in Darwin Port, Australia. Additionally, cortisol and APP (Bovine alpha 1-acid glycoprotein and Serum amyloid–A) results increased significantly (p<0.05) and were different from the baseline values taken while animals were in Darwin Port, Australia. Similarly, RMS of alpha, beta, delta, theta, Ptot and MF of the EEG were significantly (p<0.05) high during both sea and road transport. In conclusion, results of the current study revealed that the concentration of liver enzymes, total blood count, cortisol, electroencephalogram (EEG) activities and acute phase proteins (Bovine alpha 1-acid glycoprotein and Serum amyloid–A) were more detrimental by sea transport as evidenced by the significant change of the parameters above. Hence, this finding is suggestive of potential welfare problems due to animal handling and transport in relation to heat stress. Suggestively, improved animal handling during transport, stocking density and regulated vessel temperature will improve the welfare of animals subjected to long distance transport by sea.